On-Line Mobile Staff Directory Service: Implementation For The College of Arts and Sciences (CAS) - UUM. - Marian, Abdullah Mohammad Salman (2008)
Mobile Directory Services came to exist to help users to find the information they need wherever and whenever they are. With the increasing popularity of mobile communications and mobile computing, the demand for mobile directory services applications grows. This study leads to develop mobile web based directory service for college of Art and Science to provide students with information and services about lecturers or supervisors via their hand phones.